Temperature-related movement and habitat utilization patterns of Dall’s porpoises, small cetaceans seasonally migrating into the subarctic Pacific - Kanaji, Yu; Sasaki, Hiroko; Ikuta, Shun; Azuma, Noriko; Kobayashi, Mari (Frontiers in Marine Science, 2024)
Under global warming, impacts on animals’ spatial distribution in response to ocean warming have been anticipated for marine endotherms like cetaceans. Therefore, determining the distribution patterns of small cetaceans is key to understanding how their distributional patterns are susceptible to changing oceanic environments. To investigate the effect of environmental variations on distributional patterns of small cetaceans on a fine scale, we attached eight satellite tags to Dall’s porpoises bycaught in Eastern Hokkaido. After release, the tagged porpoises moved into the western North Pacific and its marginal sea, the Sea of Okhotsk. Our tagging results showed that the habitat ranges of Dall’s porpoises were restricted by water temperature. To avoid warm water, tagged porpoises changed their directions when they faced surface thermocline of 17°C. Dall’s porpoise tracked for the longest periods (116 days) showed southwestward movement after entering the Sea of Japan through the Soya Strait, while the other seven tagged porpoises stayed in the Sea of Okhotsk and off the Pacific coast around Hokkaido and Chishima islands for the entire tracking periods. Vertical movements were also recorded by these tags. Long-term tracking of Dall’s porpoises’ movement provides important insights into seasonal migration patterns, particularly for fall southward migration, which has not been well investigated compared with spring northward migration. Information on seasonal migration, distribution and percentage of time spent at the surface will improve our approach to monitoring Dall’s porpoise populations and discover important knowledge for improving the conservation and management of the population.